Reconsidering retailers' resilience and the city: A mixed method case study. (September 2022) - Hardaker, Sina; Appel, Alexandra; Rauch, Sebastian
Abstract: This study aims to better understand retailers' resilience by conducting a micro-level analysis of retailers against the backdrop of the current Covid-19 crisis. Focusing on e-commerce strategies, the paper reveals that for a better understanding of retailer's resilience it proves helpful to analytically differentiate subjective and objective aspects that influence the personal 'capacities to respond', leading to more or less (pro)active reactions (absorptive, adaptive, transformative) to the crisis. This results in the differentiation of four broad response, respectively retailer types. As such, the paper contributes to existing research frameworks by providing analytical categories for defining subjective and objective aspects of resilience as well as by applying this framework to an empirical study on retailers (and urban) resilience during the Covid-19 pandemic. A mixed method approach is applied, which includes a survey as well as expert interviews with retailers located in the German city centre of Würzburg. For urban policy makers the results provide an opportunity to redefine retail policy frameworks contributing to retailers' and urban resilience alike. Highlights: The paper contributes to existing research frameworks by providing analytical categories for defining subjective and objective aspects of resilience. A mixed method approach is applied, which includes a survey as well as expert interviews with retailers located in the German city centre of Würzburg. The paper reveals the differentiation of four broad response, respectively retailer types. For urban policy makers the results provide an opportunity to redefine retail policy frameworks contributing to retailers' and urban resilience alike.